Advances in Manufacturing II Volume 3 - Quality Engineering and Management - Hamrol, Adam; Grabowska, Marta; Maletic, Damjan; Woll, Ralf (Lecture Notes in Mechanical Engineering,, 2019)
This book covers a wide range of management issues, concerning planning, control and continuous improvement. It especially focuses on the management of the enterprise and production processes in the era of globalization, discussing the process of transferring production to developing countries, covering issues in technological culture, and reporting on quality control issues and on problems related to continuous process improvement. Modern strategies such as Six Sigma and lean manufacturing are also discussed. Another topic concerns the management of the education sphere, and how to develop the latter to prepare employees to the changes brought by the technical development. Based on papers presented at the 6th International Scientific-Technical Conference MANUFACTURING 2019, held in Poznan, Poland on May 19-22, 2019, this book bridges issues in quality engineering with concepts of ergonomics and sociology, thus offering a timely, practice-oriented guide to both the engineers and managers of the future.